Hidratação com bicarbonato de sódio não previne a nefropatia de contraste: ensaio clínico multicêntrico - Gomes, Vitor O. (2012)
BACKGROUND: Radiographic contrast media exposition can cause acute renal function impairment. There is limited and conflicting evidence that hydration with sodium bicarbonate prevents contrast-induced nephropathy (CIN) in patients undergoing cardiac catheterization. OBJECTIVE: The present study was aimed at determining whether sodium bicarbonate is superior to hydration with saline to prevent nephropathy in patients at risk undergoing cardiac catheterization. METHODS: Three hundred and one patients undergoing coronary angiography or percutaneous coronary intervention with serum creatinine > 1.2mg/dL or glomerular filtration rate (GFR) < 50ml/min were randomized to receive hydration with sodium bicarbonate starting 1 hour before the procedure and 6 hours after the procedure, or hydration with 0.9% saline. CIN was defined as an increase of 0.5mg/dL in creatinine in 48h RESULTS: Eighteen patients (5.9%) developed contrast induced nephropathy: 9 patients in the bicarbonate group (6.1%) and 9 patients in the saline group (6.0%), p = 0.97. The change in serum creatinine was similar in both groups, 0.01 ± 0.26 mg/dL in the bicarbonate group and 0.01 ± 0.35 mg/dL in the saline group, p = 0.9. No statistical difference was observed between the change in glomerular filtration rate (0.89 ± 9 ml/min vs. 2.29 ± 10 ml/min, p = 0.2 bicarbonate group and saline group, respectively). CONCLUSION: Hydration with sodium bicarbonate was not superior to saline to prevent contrast media induced nephropathy in patients at risk undergoing cardiac catheterization.